Web Service Sistem Informasi Terpadu (SIMIPA) Menggunakan REST API - Ardiansyah Ardiansyah; Didik Kurniawan; Dwi Sakethi; Bustomi bustomi; Bambang Hermanto (Jurnal Komputasi, 2021)
SIMIPA web service is a service that is used to provide services in the form of information to the Android mobile apps, is the Student module, the Lecturer module, and the Parent module. The service provided uses the REST API as a bridge between the server and the client. The goal is that the REST API can be accessed on the Android mobile apps. The development of web services in this study uses the Scrum development method which has 26 product backlogs with 9 iterations of sprints. Each sprint has several stages, namely sprint planning, daily sprint, sprint review, and sprint retrospective. Web services developed using the PHP programming language and MySQL database. The result of this research is the SIMIPA REST API which can be accessed on the Android front-end. Android accesses the REST API via the GET and POST request methods using a URL that generates a JSON response. Based on several tests, the SIMIPA REST API URL is said to have been successfully developed and can be accessed on Android mobile apps according to the expected response. Data security using the REST API is focused on the POST method using JSON Web Token (JWT).